Humanismo de Marx e industrialismo de Gramsci (Marx’s Humanism and Gramsci’s Industrialism) - Manacorda, Mario Alighiero (Revista Eletrônica de Educação, 2017)
In this conference, which took place at UFSCar, Brazil, in 1987, Manacorda refutes the contemporary tendency to dissociate Gramsci from Marx. He emphasizes the deep connections between structures and superstructures and reverses the most common understanding of the economistic aspect of structures in Marx and the humanistic aspect of superstructures in Gramsci. So, he stresses the humanistic aspect in Marx and the “industrialistic” one in Gramsci for the purpose to show the unity between being and conscience in the thought of both authors. Keywords: Marx, Gramsci, Humanism, Industrialism. Nesta conferência, proferida em 1987 no PPGE/UFSCar, Brasil, Manacorda refuta a tendência contemporânea de dissociar Gramsci de Marx. Realçando as ligações profundas entre estruturas e superestruturas e invertendo o entendimento mais comum que lê em Marx, sobretudo, o aspecto economicista das estruturas, e em Gramsci, sobretudo, o aspecto humanístico das superestruturas, Manacorda afirma em Marx o aspecto humanístico e em Gramsci o aspecto “industrialístico” para mostrar a unidade entre ser e consciência no pensamento de ambos. Palavras-chave: Marx, Gramsci, Humanismo, Industrialismo.